Peran Mahasiswa Kampus Mengajar Angkatan Empat Dalam Membantu Penataan Administrasi Sekolah di SDN 3 Pejanggik - Muhammad Sobri; Umar Umar (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to explain the role of campus students teaching batch four in assisting the management of school administration at Pejanggik 3 Public Elementary School. This research is a qualitative research with a descriptive research type. There are three data collection techniques used, namely observation, interviews, and documentation. The data analysis technique uses the Milles and Hubermen models. The conclusion drawn in this study is that there are three programs that are run at Public Elementary School 3 Pejanggik as a manifestation of the role of campus students teaching Batch 4 in assisting school administration, namely. Library arrangement, helping teachers to arrange learning tools, and school administration digital archives.